2022
DOI: 10.21203/rs.3.rs-1867762/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anchovy booms and busts linked to trophic shifts in larval diet

Abstract: Biomass fluctuations of small coastal-pelagic fishes represent perhaps the most iconic temporal record of the impacts of natural climate variability on marine ecosystems1,2,3. These fishes are key constituents of the marine pelagic food web as primary feeders on plankton, prey to higher trophic level foragers such as birds, marine mammals, piscivore fishes4,5 and valued for human consumption and industry6. Despite over a century of research, the mechanisms governing their population volatility remain elusive7,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Our results support the recent TEEL hypothesis [18]: larval feeding on prey at lower TP allowed for a more efficient energy transfer, resulting in faster growth and heavier size. We cannot rule out prey nutritional quality and larval food assimilation efficiency having some impact on the observed changes in TP [50][51][52].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results support the recent TEEL hypothesis [18]: larval feeding on prey at lower TP allowed for a more efficient energy transfer, resulting in faster growth and heavier size. We cannot rule out prey nutritional quality and larval food assimilation efficiency having some impact on the observed changes in TP [50][51][52].…”
Section: Resultssupporting
confidence: 90%
“…Moreover, rationing experiments in adult [34] and larval fishes [35,36] indicate weight increase depends greatly on feeding conditions, whereas length can increase despite sub-optimal feeding conditions. This suggests the condition of S. jordani is related to the TP of larval prey, and by extension the efficiency by which energy is transferred from the base of the food chain up to and assimilated by the larvae [18].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the heatwave was expected to help recover the declining sardine population and curb growth in an increasing anchovy population; instead, sardine abundance continued to decline throughout the heatwave (Nielsen et al, 2021), contributing to the closure of the directed fishery in 2015 (Figure 6e), while anchovy abundance rose to near record highs (Figure S3) (Thompson, Ben-Aderet, et al, 2022). Although the environmental mechanisms driving fluctuations in sardine and anchovy abundance remain poorly resolved, Swalethorp et al (2022) found that changes in larval anchovy diet explained a significant proportion of spawning stock biomass two years later. Shifting anchovy and sardine dynamics illustrate the risks of relying on historical statistical correlations to guide management decisions, as climate change increasingly results in no-analog conditions in ecosystems such as the California Current.…”
Section: Pacific Sardine and Northern Anchovymentioning
confidence: 99%
“…Prey abundance facilitates increased predator encounter rates, and Calanoids are highly abundant in temperate ocean regions worldwide (Kozak et al 2014). Historical species compositions of Calanoid populations have remained relatively stable in the CCE (Rebstock, 2001), but spatio-temporal changes in abundance, zooplankton community composition and larval distribution may nevertheless impact larval survival (Swalethorp et al, 2023, Cushing 1969).…”
Section: Discussionmentioning
confidence: 99%